Development of Wordwall-Based Assessment on Taxation Element for XI Grade of AKL Students at SMK Negeri 6 Surabaya - Nabillah Rachmadani Williantie; Suci Rohayati (JURNAL PENDIDIKAN IPS, 2025)
This study addresses the limited variety and interactivity of assessments in vocational taxation learning, especially on the topic of Income Tax (PPh Article 21). Effective and engaging assessments are essential to support student motivation and understanding, particularly in the context of the Merdeka Curriculum and increasing digital integration in education. This research aims to develop a digital-based assessment using the Wordwall platform for 11th-grade students in the Accounting and Financial Institution program at SMK Negeri 6 Surabaya. The development used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through interviews, questionnaires, and expert validations. The product was validated by assessment and graphic design experts and tested on a sample of 20 students from class XI AKL 2. Results show high feasibility, with validation scores of 93% (assessment expert) and 100% (graphic expert). Student responses were highly positive at 98%. The assessment effectively improved students’ conceptual understanding and motivation. Wordwall is recommended as an interactive and effective digital assessment alternative in vocational taxation education.